MULTIFUNGSI SISTEM USAHATANI PADI ORGANIK DAN ANORGANIK - Tinjung Mary Prihtanti, Suhatmi Hardyastuti, Slamet Hartono dan Irham (Universitas 17 Agustus 1945 Samarinda, 2013)
There is a growing public concern about the outputs of agriculture that go beyond its primary function, i.e. production of food and fibre, but how is agriculture gave impact to improving the natural resources, social, and human health? This paper reviews the emerging multifunctional farming of rice based farming system, take the case of organic farming systems (fertilizers/pesticedes natural) and inorganic (using chemical production facilities) at two location in two districts of rice cultivation, which is in the district of Karanganyar and Sragen, Central Java Province. The analysis showed that rice cultivation with organic systems provide different functions and tend to be better than the inorganic system, the togetherness among farmers, soil quality maintenance function, biodiversity, reduction of environmental pollution, and the rural viability.